Hygiene and microbial contamination along the pork value chain in Vietnam - Sinh Dang Xuan; Hung Nguyen-Viet; Phuc Pham Duc; Ngan Tran Thi; Thanh Nguyen Tien; Unger, Fred; Makita, K.; Grace, Delia (Chiang Mai University, 2015)
In Vietnam, pork accounts for 75% of total meat consumed daily at households. However, pork may contain high levels of microbial contamination such as Salmonella and Escherichia coli which might cause harm to consumers. To determine microbial contamination along the pork value chain, we collected 216 samples from 72 pig farms (floor swab, drinking and waste water), 545 from 49 slaughterhouses (carcass swab, lymph node, rectal feces, floor swab and washing water) and 514 from 220 pork shops in the informal markets (pork cuts, ground pork and cutting board swab) in 2 provinces of Vietnam (Hung Yen and Nghe An). Overall prevalence from combined all types of above mentioned samples at pig farms, slaughterhouses and pork shops for Salmonella were 35%, 30% and 37%, and for E. coli were 91%, 75% and 79%, respectively. Salmonella contamination in the final product (pork at market) was 45% and an average concentration of 9 MPN/g was recorded. E. coli average load along different points of the chain was 5.3±1.4 (farm floor swabs), 2.9±0.9 (carcass swabs), 3.1±1.0 (slaughterhouse floor swabs), and 3.3±1.1 (market shop cutting board swabs) logCFU/cm2 , whereas pork from market had 3.4±0.9 logCFU/g. Demonstrated high levels of Salmonella in the final product (pork at market) induces the potential health risks for the consumers. Detected values for E. coli indicate general poor hygiene along the chain. Appropriate hygiene practices and management are required to achieve better pork quality and reduce the risk for the consumer. These data will serve as inputs for health risk assessments related to pork consumption.